Financial inclusion: A look at the institutional and credit organisational enablers in the South African market - Gitonga, Loise (Research of GSB, 2018)
To serve the underserved markets successfully companies have to re-evaluate their strategies and approach towards the poor; this is also true for financial institutions and governments seeking to address financial exclusion or looking to fully bank the under banked in their economies. This study examines the regulatory enablers put in place by the South African government; the organisational enablers in form of financial institutions; and the products or services these institutions offer the under banked or unbanked in the society. In examining the products and services offered four factors were taken into consideration i.e. availability, acceptability, affordability and target market awareness of the product. The study was carried out using a deductive qualitative approach; the hypothesis was 'some of the macro and micro enablers required when seeking to serve the underserved are missing in South Africa'. From our analysis; there are very specific positive steps being taken to enhance the macro environment. Hopefully as these undertakings are established the micro-environment will improve. Such improvements are expected to include; increase in strong, reliable national players serving the underserved; increase in providers of good and safe services for the underserved and enhanced awareness among consumers on the products available for them.